Human hair keratin gradient metallogel and their applications for wound healing - Yee, Zhen Lin (Nanyang Technological University, 2024)
Recapitulating the microstructure of our human skin is a challenge due to the presence of heterogeneous cellular microenvironments and this challenge is accentuated when developing hydrogel scaffolds to facilitate the restoration of normal tissue function during wound healing. To alleviate these difficulties, research on developing gradient hydrogels has mushroomed. Among the fabrication strategies reported, the use of layering to develop biomimetic skin substitutes is common. One limitation is the presence of discontinuity between the layers, creating interfacial stress that can lead to delamination. This compromises the structural and functional integrity of the substitute. Another common challenge amongst other techniques is the limited scalability of the engineered constructs due to the multi-step approach with numerous equipment requirements. Moreover, synthetic materials lack inherent bioactivity and natural biomaterials create the possibility of interspecies pathogen transfers. Looking no further but to what is already present, human hair keratins (HHKs) extracted from hair waste are a sustainable source of biomaterial with scalable potential to be valorised into templates for biomedical applications. Among these templates, the use of metal ions as a hydrogelator for HHKs through the metal-thiolate complexation process has yet to be explored.